Changing Masculinities: Perspectives on Engaging Men and Boys in Gender Equality Initiatives in Tamale, Ghana - Shahadu, Abdul Somed (Université d'Ottawa / University of Ottawa, 2023)
The past three decades have seen a significant increase in the engagement of men and boys in both policies and programs that seek to promote gender equality. This response is driven in part by the realization of men's central roles in determining women's well-being, and the wider acknowledgment that earlier gender equality initiatives achieved limited success due to the exclusion of men and boys. This study builds on a growing body of scholarship that calls for increased attention to men and masculinities in gender studies, policies and programs. Even though there have been interventions aimed at engaging men and boys, the number of evaluation studies documenting the effectiveness of these interventions is inadequate. This study therefore attempts to show the significance of men's participation in gender equality programs with regards to participant perspectives and project outcomes. Central to this dissertation is the imperative for feminist policies and programs to broaden their scope to reflect the fundamental principles of social and economic justice. Programs and policies must be geared towards enacting a truly transformative vision for development that recognizes and addresses structural constraints and unequal power relations between distinct groups. The gender and development discourse since the 1970s has been premised on the fact that men occupy positions of power in many cultures and institutions of governance, and that the way in which men exercise power over women results in inequities, inequalities, discrimination, and the subordination of women. The themes emerging from the findings of this study illustrate three broad points. Firstly, resistance is significant in gender equality work in Ghana and in many parts of Africa. Secondly, change is taking place, particularly for educated men, those working in the development sector, and those who see opportunities for alternative masculinities. In the spirit of leveraging the current momentum for change, gender equality programs must be context-specific, and linked to strategies of negotiation that are culturally relevant. In other words, gender equality does not have to always mean the same thing in all places.
Keywords: Masculinities; feminism